274 LIMITATION OF ANKLE-BRACHIAL BLOOD PRESSURE INDEX FOR DIAGNOSIS OF PERIPHERAL VASCULAR DISEASE IN YOUNG AND MIDDLE-AGE ADULTS: THE BOGALUSA HEART STUDY. (1st January 2006) - Paul, T. K.; Srinivasan, S. R.; Jackson, S. A.; Raggi, P.; Chen, W.; Berenson, G. S.
Abstract : Background: Ankle-brachial blood pressure index (ABI) is a noninvasive indicator of peripheral arterial diseases (PAD) in older individuals, but information in this regard in young adults is limited. This study examined the limitation of ABI for diagnosis of PAD in asymptomatic young and middle-age adults. Methods: ABI was measured by dividing ankle systolic blood pressure by brachial systolic blood pressure obtained from a Collin machine in 867 black and white subjects (aged 24-44 years; 72% white, 44% male) enrolled in the Bogalusa Heart Study. Individuals in the bottom (ABI # 0.99; n = 44) versus top 5th (ABI 1.27; n = 50) percentile distribution of ABI were compared for traditional cardiovascular (CV) risk factors profile. Univariate analysis compared the two groups; t-tests and chi-square tests were performed. Results: There were only 6 (0.7%) individuals having clinically cut point ABI of # 0.9. Females, especially black females, had lower ABI than males (p < .0001). Blacks had lower ABI compared to whites (p < .0001). The bottom versus top 5th percentiles of ABI did not differ significantly with respect to age, body mass index (BMI), waist circumference, systolic and diastolic blood pressure, total cholesterol, LDL cholesterol, non-HDL cholesterol, HDL cholesterol, triglycerides, glucose, insulin, cigarette smoking status, and femoral and carotid intima-media thickness (IMT). In terms of prevalence of clinically defined traditional risk factors, individuals at the bottom vs top 5th percentile of ABI distribution had not had significantly higher prevalence of high LDL cholesterol, non-HDL cholesterol, triglycerides, low HDL cholesterol, high blood sugar, and high blood pressure. Further, these individuals had not had significantly higher prevalence of high BMI, waist circumference, femoral IMT, abnormal ECG, and higher smoking status. Subjects with ABI # 0.99 did not display significantly higher prevalence of multiple risk factors compared to ABI 1.27. Conclusions: The prevalence of abnormal ABI in this population is extremely low because of the relatively younger study population. The lack of association of traditionally cardiovascular risk factors with the lower ABI indicates that using ABI as a screening tool for diagnosis of PAD is not useful and cost-effective in younger and middle-age adults.